Juang Tjitjih: Pejuang Pendidikan, Ekonomi, Politik dan Emansipasi Wanita di Cianjur Tahun 1940-1964 - Maulidan, Aldi Cahya; Noeha, Oellien (Visi Sosial Humaniora, 2024)
This research examines the role and contribution of Juang Tjitjih as a female fighter in Cianjur in the period 1940-1964. The research focuses on four main areas of her struggle: education, economy, politics, and women's emancipation. This research aims to analyse and document the role and contribution of Juang Tjitjih in her struggle to advance women in Cianjur in 1940-1964 through various efforts in the fields of education, economy, politics, and women's emancipation. Through a historical research method with a biographical approach, this study analyses various primary and secondary sources, including archival documents, interviews with family and historical witnesses, and related literature. The results show that Juang Tjitjih played a significant role in advancing women's education through the establishment of women-only schools. In the economic sphere, she established women's cooperatives and skills training programmes to increase women's financial independence. In the political sphere, her contribution is reflected in her efforts to encourage women's participation in public decision-making. The women's emancipation struggle she led became an important foundation for the women's empowerment movement in Cianjur. This research concludes that Juang Tjitjih's comprehensive approach in integrating various aspects of the struggle has had a long-term impact on the progress of Cianjur society, especially women.